2018
DOI: 10.3390/molecules23102601
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin-Loaded Nanostructured Lipid Carriers for Preservation of Antioxidant Activity

Abstract: Astaxanthin is a xanthophyll carotenoid showing efficient scavenging ability and represents an interesting candidate in the development of new therapies for preventing and treating oxidative stress-related pathologies. However, its high lipophilicity and thermolability often limits its antioxidant efficacy in human applications. Here, we developed a formulation of lipid carriers to protect astaxanthin’s antioxidant activity. The synthesis of natural astaxanthin-loaded nanostructured lipid carriers using a gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 36 publications
6
45
1
Order By: Relevance
“…These findings point out the crucial role of drug incorporation, which was able to protect the drug and preserve the antioxidant activity. These results are corroborated by previous findings, which reported the improvement of the antioxidant activity of drug molecules when incorporated into lipid drug delivery systems [48][49][50].…”
Section: Samplesupporting
confidence: 91%
“…These findings point out the crucial role of drug incorporation, which was able to protect the drug and preserve the antioxidant activity. These results are corroborated by previous findings, which reported the improvement of the antioxidant activity of drug molecules when incorporated into lipid drug delivery systems [48][49][50].…”
Section: Samplesupporting
confidence: 91%
“…A polymeric matrix or a coating layer around a particular compound provides a physical barrier, preserves its biological activity, and enhances its physicochemical stability [23,35,36]. Lipid-based carriers based on microemulsion, nanoemulsion, or an association of both referred as solid lipid nanoparticles or nanostructured lipid carriers were shown to stabilize ASX [33,37,38]. A clinical trial revealed the improvement of ASX bioavailability when incorporated into a lipid-based carrier [39].…”
Section: Administration Doses and Toxicity Studiesmentioning
confidence: 99%
“…Astaxanthin, a naturally occurring keto-carotenoid, exhibits strong antioxidant and antidiabetic effects [318]. Astaxanthin-assembled nanostructured lipid carriers demonstrated the capability of improving the stability and enhancing the antioxidant activity of astaxanthin [168]. Astaxanthin-loaded chitosan oligosaccharides-PLGA core-shell nanoparticles have been found to improve the water solubility, stability, bioavailability, cytocompatibility, and sustained release profile of astaxanthin as compared to native astaxanthin [319].…”
Section: Other Plant-derived Antidiabetic Nanoformulationsmentioning
confidence: 99%